2020
DOI: 10.1038/s41598-020-77276-8
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial Hsp65 antigen delivered by invasive Lactococcus lactis reduces intestinal inflammation and fibrosis in TNBS-induced chronic colitis model

Abstract: Intestinal fibrosis associated with Crohn’s disease (CD), which a common and serious complication of inflammatory bowel diseases. In this context, heat shock proteins (HSPs) might serve as an alternative treatment because these antigens play important roles in the regulation of effector T cells. We thus evaluated the anti-inflammatory and antifibrotic capacities of an invasive and Hsp65-producing strain—Lactococcus lactis NCDO2118 FnBPA+ (pXYCYT:Hsp65)—in chronic intestinal inflammation to assess its potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Several studies already evidenced the interest in using this strain to deliver in vivo therapeutic proteins in gut inflammation. It was shown that NCDO2118 expressing mycobacterial Hsp65 reduced intestinal inflammation and fibrosis in the TNBS-induced chronic colitis model, a preclinical, experimental model of Crohn's disease (da Cunha et al, 2020). However, only the recombinant strain expressing Hsp65 was tested in vivo, and its benefits, compared with the wild-type strain, have not been assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies already evidenced the interest in using this strain to deliver in vivo therapeutic proteins in gut inflammation. It was shown that NCDO2118 expressing mycobacterial Hsp65 reduced intestinal inflammation and fibrosis in the TNBS-induced chronic colitis model, a preclinical, experimental model of Crohn's disease (da Cunha et al, 2020). However, only the recombinant strain expressing Hsp65 was tested in vivo, and its benefits, compared with the wild-type strain, have not been assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the level of the pro‐fibrotic cytokine IL‐13 could be regulated by the gut microbiota. Cunha et al showed that oral administration of Lactococcus lactis NCDO2118 FnBPA+ (pXYCYT:Hsp65) reduced the levels of IL‐13 and attenuated the degree of fibrosis in mice with TNBS‐induced colitis 46 …”
Section: Intestinal Fibrosismentioning
confidence: 99%
“…Cunha et al showed that oral administration of Lactococcus lactis NCDO2118 FnBPA+ (pXYCYT:Hsp65) reduced the levels of IL-13 and attenuated the degree of fibrosis in mice with TNBS-induced colitis. 46…”
Section: Ligands and Receptors As Anti-fibrotic Targetsmentioning
confidence: 99%
“…The gut microbe and related proteins can protect the intestine from fibrotic injury. For example, a study found heat-shock-protein 56 (HSP56) secreted by invasive Lactococcus lactis can reduce the severity of fibrosis (105).…”
Section: Involvement Of the Gut Microbiome In Intestinal Fibrosismentioning
confidence: 99%